2020
DOI: 10.1242/jcs.243477
|View full text |Cite
|
Sign up to set email alerts
|

ACSL3 is a novel GABARAPL2 interactor that links ufmylation and lipid droplet biogenesis

Abstract: While studies of ATG genes in knockout models led to an explosion of knowledge about the functions of autophagy components, the exact roles of LC3 and GABARAP proteins are still poorly understood. A major drawback for their understanding is that the available interactome data was largely acquired using overexpression systems. To overcome these limitations, we employed CRISPR/Cas9-based genome-editing to generate a panel of cells in which human ATG8 genes were tagged at their natural chromosomal locations with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Using normalized peak areas to estimate relative abundance, ATG8-PS represents approximately 10% (hLC3A) to 30% (hGABARAP) of the lipidated form, under these conditions. Similar results are also observed at endogenous expression levels (hGABARAPL2 knockin model, Figures 1I-1K) (Eck et al, 2020).…”
Section: Mass Spectrometric Analysis Of Atg8 Lipidationsupporting
confidence: 82%
See 1 more Smart Citation
“…Using normalized peak areas to estimate relative abundance, ATG8-PS represents approximately 10% (hLC3A) to 30% (hGABARAP) of the lipidated form, under these conditions. Similar results are also observed at endogenous expression levels (hGABARAPL2 knockin model, Figures 1I-1K) (Eck et al, 2020).…”
Section: Mass Spectrometric Analysis Of Atg8 Lipidationsupporting
confidence: 82%
“…HeLa cells (female, human cervical adenicarcinoma epithelial) were cultured in DMEM (GIBCO, 41966-029) supplemented with 10% FBS (Sigma) and penicillin/streptomycin (100 U/ml, 100 mg/ml; GIBCO 15140-122) at 37 C, 5% CO 2 . Wild-type and endogenously HA-tagged GABARAPL2 HeLa cells were kindly provided by Dr Christian Behrends (Eck et al, 2020). Wild-type and ATG4BÀ/À HeLa cells expressing GFP-hLC3B.G120 were kindly provided by Dr Robin Ketteler (Agrotis et al, 2019).…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Despite the discovery of UFMylation almost two decades ago, its structural basis, the full spectrum of UFMylated substrates, and its physiological role are still not fully resolved [17,40]. Studies in metazoans and our recent work have shown that UFMylation is involved in a wide range of homeostatic pathways, including ER stress tolerance, immunity, autophagy, lipid droplet biogenesis, and the DNA damage responses [14,15,23,[41][42][43][44][45][46]. In ER homeostasis, UFMylation is activated by stalling of ER-bound ribosomes and brings about the degradation of incomplete polypeptides, which can be toxic for the cell [14,23].…”
Section: Discussionmentioning
confidence: 99%
“…NMR titration experiments with wild type R1-R2-R3 325–404 peptide revealed that A371 and adjacent residues are involved in GABARAPL2 binding at high GABARAPL2 concentrations. Again, taking into account that GABARAP and LC3 protein family members are proposed to recruit UBA5 to the ER membrane and play a critical role in the regulation of the ufmylation pathway [ 33 , 41 ], these results lead to the assumption that the A371T mutation plays a minor role in the ufmylation reaction itself, but might affect UBA5 localization and thus influences target ufmylation.…”
Section: Discussionmentioning
confidence: 99%